THE DISTINCT AND AGGRESSIVE PATHOGENESIS OF ARTHRITIS IN CHILDREN WITH DOWN SYNDROME - Foo, Serena Shuk Yeng (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2023)
Juvenile idiopathic arthritis (JIA) is the most common form of inflammatory arthritis (IA) in children. However, recently we described a more aggressive form of IA in children with Down syndrome (DS), termed Down syndrome associated Arthritis (DA). DA is 20 times more common than JIA, occurring at a rate of 1/50 in children with DS. The early diagnosis and treatment of IA in children is critical for long-term joint health and normal growth. However, the diagnosis of IA in children with DS is extremely challenging. As a result, it is rarely recognised at onset, and is under-diagnosed. Therefore, by the time these children attend a Rheumatology Clinic, they may already have significant joint damage. While many children with DA respond to current treatments, a significant proportion do not respond or have adverse side effect. Therefore, new treatment strategies along with better approaches for early diagnosis are required so that these children can be treated early with the right treatment from the onset, which ultimately will lead to improved quality of life. However, little is known about the proteins, genes and cells that are involved in driving inflammation in the inflamed joint from children with DA. Therefore, this thesis examined immune cells in the blood from children with DA, in addition to specific cells in the joint tissue called synovial fibroblasts (which are the cell type that invade the cartilage and bone) and endothelial cells which allow bad immune cells to enter the joint from the circulation. Initially we demonstrated that three key proinflammatory proteins induce the synovial fibroblasts to become more invasive, which facilitates their ability to breakdown cartilage and bone within the joint. Furthermore, these proteins activate endothelial cells which allows the immune cells to enter the joint. These immune cells do not function properly and produce more proinflammatory proteins that further enhance the inflammatory response in the joint. This causes the joint tissue to swell resulting in more pain and subsequent disability if not treated early. Interestingly, two of these proteins acted together in their ability to induce inflammation, and this has implications for treatment strategies as targeting both may produce better outcomes. We next identified that synovial fibroblasts and endothelial cells altered the way they use energy within the cell, a process that allows them to maintain their pathogenic inflammatory state. We showed that blockade of these energy pathways, led to resolution of inflammation, therefore there is potential to develop medicines that target both these specific dysfunctional pathways. Finally, we examined immune cells in the circulation of children with DA. We demonstrated that a specific immune cell called a T cell is more activated in children with DA compared to JIA or healthy controls. Indeed, these particular T cells produce more proinflammatory proteins simultaneously, and are known therefore to be more potent in driving the inflammatory response but are also more resistant to treatment. Interestingly, the two most dominant proinflammatory proteins being produced by these T cells are the same two proteins that together drive synovial fibroblast and endothelial cells’ function. Thus, the research in this thesis represents a significant advancement in our understanding of the disease and identifies distinct immune-synovial cell dysregulation in the pathogenesis of DA. In particular, these data have potential implications for combination therapy or manipulation of metabolic pathways for the treatment of DA. Further studies and support for this condition, will lead to improved diagnostic and prognostic outcomes for these vulnerable children. It also demonstrates the importance of translational research, and the involvement of patients with research, thus we would like to thank the children and their parents as this research could not have been performed without them.
APPROVED
Keywords: arthritis; down syndrome; cytokines; immunology; fibroblasts; adaptive immune system